Analisis Hukum terhadap Hak Pekerja Migran Indonesia yang Mendapat Kekerasan saat Bekerja - Anggie Febriani; Oremia Exilla Rafelina Sihombing; Bintang, Citra; Tarina, Dwi Desi Yayi (VISA: Journal of Vision and Ideas, 2024)
This study aims to analyze the legal protection for Indonesian migrant workers who experience violence while working abroad. The research method used is normative with a descriptive-analytical approach, examining relevant legislation, literature, and expert legal opinions. Data were collected through primary and secondary legal sources and analyzed qualitatively. The results show that although Law No. 18 of 2017 on the Protection of Indonesian Migrant Workers provides comprehensive protection for migrant workers, cases of violence against them still frequently occur. The government, through the Indonesian Migrant Worker Protection Agency (BP2MI), has a significant responsibility in providing protection, legal assistance, and support for migrant workers who experience violence. BP2MI collaborates with various parties to handle cases of violence and ensure the rights of migrant workers are fulfilled. The conclusion of this study is the need for increased efforts in protection and continuous monitoring by the government, as well as stronger international cooperation to reduce and address cases of violence against Indonesian migrant workers abroad.